Analysis of anterior corneal surface shape after replacing orthokeratology lenses carrying a small base curve diameter - Chen, Minfeng; Zhao, Sijun; Peng, Lulu; Rong, Yu; Zhu, Chengwei; Lu, Fan; Mao, Xinjie (Frontiers in Neuroscience, 2024)
PurposeThe study analyzed the changes in corneal surface shape after replacing orthokeratology lenses carrying a small base curve (BC) diameter.MethodsIn this retrospective study, we included ~54 right eyes belonging to 54 myopic children who insisted on wearing an orthokeratology (ortho-k BC 6.0 mm) lens for more than 12 months and then replaced the second ortho-k (BC 6.0 mm or BC 5.0 mm) lens ~12 months. The children were categorized into two groups based on the design of the BC of the replaced ortho-k lens 6.0/5.0 and 6.0/6.0.ResultsThe ratio of axial length (AL) elongation in the 6.0/5.0 group was significantly less than in the 6.0/6.0 group (−0.015 ± 0.014 mm/M vs. −0.005 ± 0.012 mm/M, t = −2.672, P = 0.010). After replacing the BC 5.0 ortho-k lens, the optical zone (8.19 ± 2.60 mm2 vs. 9.64 ± 1.57 mm2, t = −2.345, p = 0.023), reverse zone (31.64 ± 5.80 mm2 vs. 34.86 ± 4.61 mm2, t = −2.169, p = 0.035), and treatment zone (17.16 ± 3.94 mm2 vs. 22.96 ± 2.59 mm2, t = −6.049, p < 0.001) were all smaller than those in the 6.0/6.0 group. In the 6.0/5.0 group, the optical zone (wearing more than 1 month as first: 11.16 ± 2.12 mm2, the last inspection before replacing lens as before: 10.87 ± 1.90 mm2), reverse curve zone (first: 22.03 ± 3.11 mm2, before: 26.24 ± 5.06 mm2), and treatment zone (first: 35.97 ± 5.54 mm2, before: 37.11 ± 6.04 mm2) were all greater than these after replacing ortho-k lens (all P < 0.001).ConclusionReplacing an ortho-k lens with a smaller BC resulted in a larger decrease in the mean central corneal zone and a substantial increase in the paracentral corneal zone. In addition, the ortho-k lens with a smaller BC does not increase the decentration distance and contributes to effective myopia control.